2016
DOI: 10.18632/oncotarget.8395
|View full text |Cite
|
Sign up to set email alerts
|

The novel JNK inhibitor AS602801 inhibits cancer stem cells in vitro and in vivo

Abstract: A phase 2 clinical trial investigating the efficacy and safety of AS602801, a newly developed JNK inhibitor, in the treatment of inflammatory endometriosis is complete. We are now examining whether AS602801 acts against human cancer cells in vitro and in vivo. In vitro, AS602801 exhibited cytotoxicity against both serum-cultured non-stem cancer cells and cancer stem cells derived from human pancreatic cancer, non-small cell lung cancer, ovarian cancer and glioblastoma at concentrations that did not decrease th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
74
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(74 citation statements)
references
References 37 publications
0
74
0
Order By: Relevance
“…CC‐930 is being tested in idiopathic pulmonary fibrosis and high‐dose CC‐930 caused elevation of hepatic transaminases when used for long‐term treatment . AS602801 is being tested in endometriosis and demonstrated favorable safety and tolerability after 5 months of administration . Both diseases are benign, chronic inflammatory diseases, and the efficacy of the inhibitors has not been examined in malignant tumor patients; our results suggest that it is worth examining the safety and tolerability in those patients.…”
Section: Discussionmentioning
confidence: 89%
“…CC‐930 is being tested in idiopathic pulmonary fibrosis and high‐dose CC‐930 caused elevation of hepatic transaminases when used for long‐term treatment . AS602801 is being tested in endometriosis and demonstrated favorable safety and tolerability after 5 months of administration . Both diseases are benign, chronic inflammatory diseases, and the efficacy of the inhibitors has not been examined in malignant tumor patients; our results suggest that it is worth examining the safety and tolerability in those patients.…”
Section: Discussionmentioning
confidence: 89%
“…In the present study, we also found that the expression levels of the TFAM and c‐Myc proteins in GSCs were higher than those detected in isogenic differentiated GSCs. Moreover, studies by us and others previously demonstrated that the c‐Myc protein levels were elevated in CSCs including GSCs and that high c‐Myc expression and activity were implicated in the maintenance of CSC properties . Therefore, the c‐Myc/TFAM/complex III/complex IV axis in GSCs is a candidate for effective, safe and specific therapeutic targets.…”
Section: Discussionmentioning
confidence: 96%
“…Viable and dead cells were identified by their ability and inability to exclude vital dyes, respectively . Briefly, cells were treated with drugs as described and stained with 0.2% trypan blue for 1 min at room temperature (RT), and the number of viable and dead cells was determined using a haemocytometer.…”
Section: Methodsmentioning
confidence: 99%
“…[80] In another report, the JNK1 (c-Jun N-terminal kinase) inhibitor bentamapimod was shown to exhibit growth-inhibitory effects in CSCs derived from xenografts of human pancreatic, non-small cell lung and ovarian cancers, and from glioblastoma. [82] However, the mechanism of action leading to the apparent specificity for CSCs remains to be fully elucidated. Finally, repertaxin, a CXCR1 (interleukin 8 receptor) inhibitor, could target breast CSCs, and the same effect was observed with a CXCR1-specific antibody.…”
Section: Miscellaneousmentioning
confidence: 99%